The model of determining the sensitivity of elements of multiple criteria evaluation methods - Dėjus, Titas (Journal of Civil Engineering and Management, 2002)
Multipurpose version construction design under market conditions has no alternatives as only having formed sufficient quantity of variants to choose a rational, if not optimal, variant, which implemented will result in a priori known or enough close results. Performed calculations enable to state that the ideal point method is much more sensitive to changes of separate parameters and, applying the above-named method, it is necessary to take into account the fact that final result is effected by both decision matrix elements, indices importance parameters and also mathematical apparatus of the applied method. SAW method is sensitive to changes of separate parameters only, and sensitivity of mathematical apparatus may be defined as absolute ultimate insensitivity. The proposed model for determining methods of sensitivity to changes of separate parameters enables to increase the reliability of applied methods and expands opportunities for application of the theory of multipurpose evaluation methods in construction technology.Frist Published Online: 30 Jul 2012